On the dispersion of waves in an elastic layer carrying the layer of a viscous fluid - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the base of the three-dimensional linearized Navier–Stokes equations for a viscous fluid and the linear equations of classical theory of elasticity for an elastic layer, the dispersion curves are constructed, and the propagation of acoustic waves within the wide range of frequencies is studied. An effect of the viscosity of a fluid, the thicknesses of elastic and fluid layers on the phase velocities and the attenuation coefficients of modes are analyzed for both thin and thick elastic layers.